ANALISIS RETURN, ABNORMAL RETURN, AKTIVITAS VOLUME PERDAGANGAN DAN BID-ASK SPREAD SAHAM DI SEPUTAR PENGUMUMAN STOCK SPLIT (Studi pada Perusahaan Manufaktur di BEJ) - M. TAUFIQ NOOR ROKHMAN; Didied P. - Affandy; S.M. KIPTIYAH - - (Sekolah Pascasarjana Universitas Brawijaya, 2009)
ABSTRACT Event study is a study which analyze any market reactions to an event which its information is published as announcement. The stock split can influence the market depend on the existence of the content of the information in the stock split phenomenon or not. If the stock split contains information then the market will react and vice versa. The objective of this research is to find out the difference of return, abnormal return, trade volume activity, and stock’s bid-ask spread before, in the moment, after the stock split announcement. The research sample is done by purposive sampling method, and there are 24 manufacturing companies which announce stock split between 1999-2001. Statistical experiment used is T-test experiment (paired two samples for means). The Observation period which is done in 11 day, consist of 5 day before, 1 day in the moment, and 5 day after the stock split. The result of this research shows that there is a significant difference between return and abnormal return in the period of between at the moment, and after the stock split. The result in the before-after stock split period shows that there is no significant difference. The result in the variable activity of stock’s trade volume shows that there is no signification difference in the before-at the moment and after period, but in the result of before-after period show that there is significant difference there. And the result of bid-ask spread variable shows that there is significant different in the before-at the moment and after period of stock split, but in the before-after period the result shows that there is no significant different there. And the result of bid-ask spread variable shows that there is significant different in the before-at the moment and after period of stock split, but in the before-after period the result shows that there is no significant different there. Cumulatively, this research gives a conclusion that stock split have no information contents so that the market in general give no reaction. But, the stock split it self can influence the level of stock’s liquidity which has possibility to press on the ownership proportion of the old investor. Key Word: Stock split, Return, Abnormal return, TVA and Bid-ask Spread